Probing Spatial Proximity of Supported Lipid Bilayers to Silica Surfaces by Localized Surface Plasmon Resonance Sensing - Ferhan, Abdul Rahim (2017)
On account of high surface sensitivity, localized surface plasmon resonance (LSPR) sensors have proven widely useful for studying lipid membrane configurations at solid–liquid interfaces. Key measurement capabilities include distinguishing adsorbed vesicles from supported lipid bilayers (SLBs) as well as profiling the extent of deformation among adsorbed vesicles. Such capabilities rely on detecting geometrical changes in lipid membrane configuration on a length scale that is comparable to the decay length of the LSPR-induced electromagnetic field enhancement (∼5–20 nm). Herein, we report that LSPR sensors are also capable of probing nanoscale (∼1 nm) variations in the distance between SLBs and underlying silica-coated surfaces. By tuning the electrostatic properties of lipid membranes, we could modulate the bilayer–substrate interaction and corresponding separation distance, as verified by simultaneous LSPR and quartz crystal microbalance-dissipation (QCM-D) measurements. Theoretical calculations of the expected variation in the LSPR measurement response agree well with experimental results and support that the LSPR measurement response is sensitive to subtle variations in the bilayer–substrate separation distance.